Pendidikan Islam Multikultural sebagai Kerangka Teoretis Pembangunan Sosial Inklusif: Studi Pemikiran KH Muhammad Tholhah Hasan - Agus Makmun; Nur Cholid; Muh. Syaifudin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study examines the concept of multicultural Islamic education in the thought of KH Muhammad Tholhah Hasan as a theoretical framework for inclusive social development. The background of this research is the increasing social, cultural, and religious plurality that demands an educational approach capable of strengthening social cohesion and inclusivity. This study employs a qualitative approach with a library research design. Data were collected through documentation of primary sources in the form of KH Muhammad Tholhah Hasan’s works, as well as secondary sources consisting of scholarly books and journal articles relevant to Islamic education, multiculturalism, and social development. Data analysis was conducted using content analysis and thematic analysis to identify core concepts, values, and theoretical propositions. The findings indicate that KH Muhammad Tholhah Hasan conceptualizes Islamic education not merely as a means of transmitting religious doctrine, but as an instrument for internalizing ethical values, social responsibility, and public morality grounded in Islamic teachings. Multiculturalism is understood as an ethical praxis rooted in Islamic values rather than moral relativism. This study concludes that multicultural Islamic education in KH Muhammad Tholhah Hasan’s thought functions as a cultural mechanism that strengthens social cohesion and supports inclusive social development. The novelty of this research lies in positioning Islamic multicultural education as a theoretical foundation for inclusive social development based on a Muslim intellectual’s thought